A high performance triboelectric nanogenerator for self-powered non-volatile ferroelectric transistor memory. Issue 41 (9th September 2015) - Fang, Huajing; Li, Qiang; He, Wenhui; Li, Jing; Xue, Qingtang; Xu, Chao; Zhang, Lijing; Ren, Tianling; Dong, Guifang; Chan, H. L. W.; Dai, Jiyan; Yan, Qingfeng
Abstract : We demonstrate an integrated module of self-powered ferroelectric transistor memory based on the combination of a ferroelectric FET and a triboelectric nanogenerator (TENG). Abstract : We demonstrate an integrated module of self-powered ferroelectric transistor memory based on the combination of a ferroelectric FET and a triboelectric nanogenerator (TENG). The novel TENG was made of a self-assembled polystyrene nanosphere array and a poly(vinylidene fluoride) porous film. Owing to this unique structure, it exhibits an outstanding performance with an output voltage as high as 220 V per cycle. Meanwhile, the arch-shaped TENG is shown to be able to pole a bulk ferroelectric 0.65Pb(Mg1/3 Nb2/3 )O3 –0.35PbTiO3 (PMN-PT) single crystal directly. Based on this effect, a bottom gate ferroelectric FET was fabricated using pentacene as the channel material and a PMN-PT single crystal as the gate insulator. Systematic tests illustrate that the ON/OFF current ratio of this transistor memory element is approximately 10 3 . More importantly, we demonstrate the feasibility to switch the polarization state of this FET gate insulator, namely the stored information, by finger tapping the TENG with a designed circuit. These results may open up a novel application of TENGs in the field of self-powered memory systems.